2004
DOI: 10.1037/0021-9010.89.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Penalties for Success: Reactions to Women Who Succeed at Male Gender-Typed Tasks.

Abstract: A total of 242 subjects participated in 3 experimental studies investigating reactions to a woman's success in a male gender-typed job. Results strongly supported the authors' hypotheses, indicating that (a) when women are acknowledged to have been successful, they are less liked and more personally derogated than equivalently successful men (Studies 1 and 2); (b) these negative reactions occur only when the success is in an arena that is distinctly male in character (Study 2); and (c) being disliked can have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
954
7
18

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 978 publications
(1,015 citation statements)
references
References 31 publications
36
954
7
18
Order By: Relevance
“…9,17,18 Performing a meta-analysis of experimental studies in which only the sex of the leader varied, Eagly et al 19 found that women leaders who adopted a stereotypically masculine, autocratic style received lower evaluations than men exhibiting the same style of leadership. Heilman et al, 11 in a randomized study where evaluators rated assistant vice presidents for identical accomplishments, found that women but not men who were competent in leadership positions typically held by men were viewed as unlikable and that competence and likability were independent predictors of being recommended for institutional rewards. Butler and Geis 17 found that when women perform as a single leader in a work group, they are subject to more subtle negative affective responses from other members of the team than men following identical scripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,17,18 Performing a meta-analysis of experimental studies in which only the sex of the leader varied, Eagly et al 19 found that women leaders who adopted a stereotypically masculine, autocratic style received lower evaluations than men exhibiting the same style of leadership. Heilman et al, 11 in a randomized study where evaluators rated assistant vice presidents for identical accomplishments, found that women but not men who were competent in leadership positions typically held by men were viewed as unlikable and that competence and likability were independent predictors of being recommended for institutional rewards. Butler and Geis 17 found that when women perform as a single leader in a work group, they are subject to more subtle negative affective responses from other members of the team than men following identical scripts.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, many controlled studies confirm that women who violate behavioral gender norms (e.g., highly assertive women or women in positions of authority) often suffer social penalties in the work place, such as being less liked or more personally derogated than equivalently successful men. [9][10][11][12] Residency is the first time during training that new physicians are thrust into a directive leadership role in which they must routinely assert influence. Residents must effect patient care by giving orders and making requests of other members of the healthcare team, including nurses, pharmacists, and other physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Deprivation of any of these factors has been shown to be related to a number of undesirable psychological and physiological effects (e.g., Cross & Vick, 2001;Uchino, Cacioppo, & Kiecolt-Glaser, 1996) and, as discussed previously, may itself lead to lower interest in the activities. Perhaps women in male-dominated areas do not affiliate with other women in the field for fear of being implicated by a negative gender stereotype association (Heilman, Wallen, Fuchs, & Tamkins, 2004). Intervention programs (such as the Women in Engineering Initiative) that recruit and consistently make contact with women in male-dominated fields appear to provide a safe and structured environment for women to interact and consequently enhance field retention rates (e.g., Brainard & Carlin, 1998;Downing, Crosby, & Blake-Beard, 2005).…”
Section: Women In Math and Science Fieldsmentioning
confidence: 99%
“…On the one hand, although considerable research demonstrates gender bias in a variety of other domains (19)(20)(21)(22)(23), science faculty members may not exhibit this bias because they have been rigorously trained to be objective. On the other hand, research demonstrates that people who value their objectivity and fairness are paradoxically particularly likely to fall prey to biases, in part because they are not on guard against subtle bias (24,25).…”
mentioning
confidence: 99%